The christians of the Middle East and the role of their “conspiracy” in the Archipelago expedition of the Russian navy in 1769–1774 - Taras Kobishchanov (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The history of the fi rst military and political contacts between Russia and the Arab world has long been ignored by Russian orientalists. The reason was the unwillingness to introduce the “imperialistic” component to the untainted history of Soviet-Arabic relations. Due to the studies of the recent past, we have a relatively full picture of both the course of events of 1770‒1774 and changes in the political agenda that urged local rules to enter a union with Russia. However, the reasons that underlay the alliance of Near Eastern rulers with a Christan state cannot be reduced to just basic political and economical factors. A prominent role was also played by the religious and ideological component, which is described in the article.